Koefisien perpindahan massa keseluruhan volumetris pada kolom ekstraksi mixer-settler - Perpustakaan UGM, i-lib ([Yogyakarta] : Badan Kerjasama Penelitian dan Pengembangan Pariwisata, 2002)
BSTRAK The volumetric over-all mass transfer coefficient (K,.a) in a single stage mixer-settler column has been investigated. In the measurement of K,.a. acetic acid was extracted from kerosene-acetic acid solution into water. The mixer-settler column used in this experiment was divided into a mixer of 5.8 em height and a settler of 5.5 em height separated by a drop coalescer. The column diameter was 10.2 em. The diameter of drop coalescer was 5 em. I em in height. with the holes diameter of I mm. The values of K,.a were affected by the volumetric rates of the continuous and dispersed phases and also by agitation speed. These data can be correlated by Sh,. = 8.75 X /0,/11 Re.o.3/ Relf>2 Re/46 in the ranges of ReI' of 149.18358.63. Red of 51.18-296.91. and Rei of 5.639.12-11.280.06 with the relative mean error of 11.32%. Keywords: volumetris, kolom ekstraksi, Mixer-Settler